Intraocular Lens Power Calculation Without Corneal Parameters: A New Option. Issue 4 (April 2021) - Rosa, Nicola; Zeppa, Lucio; De Bernardo, Maddalena; Coppola, Alessia; Zeppa, Lucia; Borrelli, Maria
Abstract : Objectives: To compare different methods in calculating the corneal radius (R) to be used in case of intraocular lens power calculations when it is immeasurable. Methods: The right eyes of 1, 960 patients were randomly divided into 2 equal groups. The first group of right eyes (group A) was divided in three groups according to the axial length (AL) (⩽21.99 mm, between 22 and 24.99 mm, and ≥25 mm). In these groups, the correlation between the AL and the corneal radius (R) provided three different regression formulas. The second group of right eyes (group B) was used to test the following methods of estimating the R: the regression formulas determined from group A, formula from Logan et al., formula from Stenström, the mean R calculated from group A, and the fellow eye group B. A Student paired T test was used for the statistical evaluation. Results: In case of AL⩽21.99, the best results have been obtained with the fellow eye R, followed by either the regression formula or the mean R from group A (mean=0.00±0.09 mm, P =0.94, mean=0.05±0.21 mm, P =0.05, mean=0.05±0.22 mm, P =0.08, respectively). In case of AL between 22 and 24.99 mm, the best results have been obtained with the fellow eye R, followed by either the regression formula or the mean R from group A (mean=−0.01±0.09 mm, P =0.38, mean=0.01±0.21 mm, P =0.12, mean=0.01±0.24 mm, P =0.18, respectively). In case of AL≥25 mm, the best results have been obtained with the fellow eye R, followed by either the regression formula or the mean R from group A (mean=−0.003±0.08 mm, P =0.94 mean=−0.004±0.25 mm, P =0.85, mean=−0.004±0.25 mm, P =0.85, respectively). Conclusions: The new calculated regression formulas seem to represent a reliable method to calculate the R when it is undetectable, as in case of corneal dystrophies.